Hepatic epithelioid hemangioendothelioma: A clinocopathological correlation - Apurva Dale Mundada; Kedar Deodhar; Mukta Ramadwar; Munita Bal; Rajiv Kumar (Wolters Kluwer Medknow Publications, 2022)
Primary hepatic epithelioid hemangioendothelioma (HEHE) is a rare tumor with an incidence of <0.1 per 100,000. The clinical course is variable with variable outcomes. Due to its rarity, treatment protocols, prognostic and predictive factors are not well established underscoring the need for such a study. Pathologists' awareness of this entity, a meticulous morphologic examination coupled with immunohistochemistry can aid in accurate diagnosis.